Doxorubicin Changes Bax /Bcl-xL Ratio, Caspase-8 and 9 in Breast Cancer Cells - Simin Sharifi; Jaleh Barar; Mohammad Saeid Hejazi; Nasser Samadi (Tabriz University of Medical Sciences, 2015)
Purpose: Doxorubicin is administrated as a single agent in first-line therapy of breast cancer to induce apoptosis in tumor cells. Bax, Bcl-xL, Caspase-8 and 9 proteins are involved in induction of apoptosis. The present study describes Bax, Bcl-xL gene expression and Caspase-8 and 9 protein levels in MCF-7 cells incubated with doxorubicin at different doses an incubation times. Methods: The cytotoxic effects of doxorubicin were studied using MTT assay. MCF-7 cells were treated with three concentrations of doxorubicin (0.1, 0.5, 1 μM) and incubated for 24, 48 and 72 hours then expression levels of Bax and Bcl-xL genes were elucidated by Real-time RT-PCR technique and protein levels of caspase-8 and caspase-9 proteins were measured using ELISA method. Morphological modifications of the cells were also monitored via light microscopic images. Results: Doxorubicin decreased the anti-apoptotic Bcl-xL and increased pro-apoptotic Bax mRNA levels. Doxorubicin induced a significant increase in Bax /Bcl-xL ratio in all doses and incubation times (p<0.05). Highest (more than 10 fold) increase in Bax /Bcl-xL ratio was revealed after 48 h incubation of the cells with in all doses of doxorubicin. Doxorubicin also increased caspase-9 level in a time and dose-dependent manner, while caspase-8 level didn't follow time and dose dependency pattern. Conclusion: Our results confirm that doxorubicin induces mitochondrial-dependent apoptosis by down-regulation of Bcl-xL and up- regulation of Bax and caspase-9 expressions.